Hubungan antara aktivitas fisik dan kualitas tidur dengan stress di masa pandemi COVID-19 - Ichwantoro, Syahwal; Chondro, Fransisca (Jurnal Biomedika dan Kesehatan, 2022)
BACKGROUND The COVID-19 pandemic has impacted negatively on lives all around the world. Indonesia implemented physical distancing and lockdown to prevent the spread of this virus. However, without realising it, the implementation of these rules can have a negative effect on physical and mental health, including stress. In a study of 113.285 people conducted in China, India, Spain, Italy, and Iran, stress was found to be prevalent in 53% of the population. Sudden changes in lifestyle (physical distancing and lockdown) can lead to less physical activity and poor sleep quality, both of which can lead to stress. Physical activity and sleep quality in the context of stress give inconsistent results. Therefore, researchers are interested in examining the correlation between physical activity and sleep quality with the incidence of stress during the COVID-19 pandemic. METHODS This study was using a cross-sectional approach and the subject of this study were teachers. In this study, physical activity was measured using the International Physical Activity Questionnaire Short Form, sleep quality was measured using the Pittsburgh Sleep Quality Index, and stress was measured using the Perceived Stress Scale. The data obtained was analysed using the chi-square and kolmogorov-smirnov test with a significance limit <0.05. RESULTS Based on the data obtained from this study, it can be concluded that 54.1% subjects have a moderate physical activity, 90.2% subjects have a poor sleep quality, and 60.7% subjects have a mild stress level. Statistical analysis between physical activity and stress obtained p = 1.0 and between sleep quality and stress obtained p=0.883. CONCLUSIONS According to the study's findings, there is no statistically significant correlation between physical activity and stress, and there is no correlation between sleep quality and stress during the COVID-19 pandemic. KEYWORDS: COVID-19, Physical Activity, Sleep Quality, Stress